Cortical depth-dependent temporal dynamics of the BOLD response in the human brain - Siero, Jeroen C W (Nature Publishing Group, 2011)
Recent animal studies at high field have shown that blood oxygen level-dependent (BOLD) contrast can be specific to the laminar vascular architecture of the cortex, by differences in its temporal dynamics in reference to cortical depth. In this study, we characterize the temporal dynamics of the hemodynamic response (HDR) across cortical depth in the human primary motor and visual cortex, at 7 T and using very short stimuli and with high spatial and temporal resolution. We find that the shape and temporal dynamics of the HDR changed in an orderly manner across cortical depth. Compared with the pial vasculature, HDRs in deeper gray matter are significantly faster in onset time (by ∼0.5 second) and peak time (∼2 seconds), and are narrower (by ∼1 second) and with smaller amplitude, in line with the known vascular organization across cortical depth and the transit of deoxygenated blood through the vasculature. The width of the HDR in deeper gray matter was as short as 2.1 seconds, indicating that neurovascular coupling takes place at a shorter timescale than previously reported in the human brain. These findings open the possibility to probe layer-specific hemodynamics and neurovascular coupling mechanisms in human gray matter.